2021
DOI: 10.1155/2021/6736008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and a Nomogram Predicting Overall Survival and Cancer-Specific Survival for Patients with Collecting Duct Renal Cell Carcinoma

Abstract: Background. Collecting duct renal cell carcinoma (CDRCC) is a rare type of renal cancer characterized by a poor prognosis. The aim of this work was to develop a nomogram predicting the overall survival (OS) and cancer-specific survival (CSS) for patients with CDRCC. Methods. A total of 324 eligible patients diagnosed with CDRCC from 2004 to 2015 were identified using the data from the Surveillance, Epidemiology, and End Results (SEER) database. The Kaplan-Meier curve was used to estimate the 1-, 3-, and 5-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…For patients in good condition, surgery can significantly reduce tumor burden and prolong overall survival ( 29 ). Collecting duct renal cell carcinoma (cdRCC) and sarcomatoid renal cell carcinoma (sRCC) were associated with an aggressive biology and characterized by a poor prognosis ( 30 , 31 ). Consistent with previous studies, histological classification such as cdRCC and sRCC was significantly related to early death of mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…For patients in good condition, surgery can significantly reduce tumor burden and prolong overall survival ( 29 ). Collecting duct renal cell carcinoma (cdRCC) and sarcomatoid renal cell carcinoma (sRCC) were associated with an aggressive biology and characterized by a poor prognosis ( 30 , 31 ). Consistent with previous studies, histological classification such as cdRCC and sRCC was significantly related to early death of mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large cohort studies revealed that for CDC patients, CSS was similar to OS. This indicates that a vast majority of CDC patients eventually die due to CDC, further reflecting poor prognosis of CDC 4 , 7 . In the current study, the median OS and CSS time for CDC patients were 5 and 6 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is often chosen for management of CDC based on established standard treatments for common renal tumors. Previous studies demonstrated that patients receiving surgery survive longer than those who do not undergo surgery for CDC 4 , 7 . However, metastatic features of the tumor may prevent this potential survival benefit obtained from surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As the result, when patients intend to seek a healing care, they may have been in a metastatic state of kidney cancer and are suffering from the corresponding complications. e fiveyear survival rates of stage I and II were about 88% to 95%, and cancer-specific survival (CSS) rates were 84% to 95% [4]. Renal cell carcinoma (RCC), making up 90% of kidney cancer, is the sixth and eighth most common cancer among American men and women in 2021 [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of initial diagnosis, 18%-40% of patients have already developed systemic metastases. In addition, metastasis is widespread in the long-termfollow-up after nephrectomy [4,7,9,13,14]. e study of Jianxin Xue and colleagues reported that 2931 of 33449 RCC had distant metastasis and lung (6.19%) was the most common site of metastasis [7].…”
Section: Introductionmentioning
confidence: 99%